Subcortical Low Intensity on MR Images of Meningitis, Viral Encephalitis, and Leptomeningeal Metastasis - Lee, Jae Hee; Na, Dong Gyu; Choi, Kyu H.; Kim, Ki Jun; Ryoo, Jae Wook; Lee, Sung Yong; Suh, Yeon-Lim (American Journal of Neuroradiology, 2002)
BACKGROUND AND PURPOSE: Subcortical low-intensity lesion on T2-weighted images is an uncommon manifestation of ischemia, multiple sclerosis, and Sturge-Weber disease. This study was performed to determine whether subcortical low signal intensity is an MR feature of meningitis, viral encephalitis, or leptomeningeal metastasis and to investigate a cause of subcortical low intensity.METHODS: We retrospectively reviewed MR images of 117 patients with meningitis, encephalitis (viral or unknown), or leptomeningeal metastasis for the presence of subcortical low intensity, meningeal enhancement, signal intensity change of cortex, and change in subcortical low intensity on follow-up images. Diffusion-weighted (DW) images and apparent diffusion coefficient (ADC) maps were obtained in 55 patients. Subcortical low-intensity lesions were also quantitatively analyzed on T2-weighted, fluid-attenuated inversion recovery (FLAIR), and DW images.RESULTS: Subcortical low intensity was found in nine (23.7%) of 38 patients with encephalitis (viral, 31; unknown origin, 7), five (24%) of 21 with leptomeningeal metastasis, and five (9%) of 58 with meningitis. Leptomeningeal enhancement was observed in 100% and cortical hyperintensity in 14 (74%) of 19 patients with subcortical low intensity. Leptomeningeal enhancement was seen in 46 (47%) and cortical hyperintensity in 33 (34%) of 98 patients without subcortical low intensity. Subcortical low intensity disappeared or decreased in extent on follow-up MR images in all seven patients who underwent follow-up. ADC of subcortical low-intensity lesions was lower than that of the contralateral area and decreased by 9.3 ± 11.4%.CONCLUSION: Subcortical low intensity was uncommonly found in meningitis, viral encephalitis, and leptomeningeal metastasis. It is a nonspecific MR sign of various meningeal and cortical diseases. Although the cause of subcortical low intensity remains uncertain, free radical formation may play a role as a causative factor.